(untitled) (Economics and region, 2019)
The paper deals with the analysis of the main perspectives of green investments market functioning in Ukraine. The dynamic and tendency of functioning of the Ukrainian and EU green market investment market were analysed. In the paper the main approaches to defining green investment, principals and features of green investment market functioning were consolidated. Besides, the main players and its roles were indicated in the paper by the author. The results of analysis of the Ukrainian green investment market functioning showed that the main barriers which restrict the developing were: insufficient of the legal basis; misunderstanding of the main features of green investment among investors; the lack of government support in Ukraine and etc. In the paper, the main categories of green investment were summarised. The conceptual framework of transformation from traditional to green investment market in Ukraine was proposed. With the purpose to indicate the main directions for developing the Ukrainian green investment market, the European Union experience of green investment market functioning were analysed. The findings showed that the most attractive directions for green investment are clean energy and green securities. In this case, the dynamic of green bonds market was analysed. On the basis of the findings the main attractive directions for green investment in Ukraine were indicated.